2017
DOI: 10.15547/tjs.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Study of genetic parameters and association between characters in einkorn genotypes

Abstract: The study is carried out in the experimental field of Institute of Plant Genetic Resources "Konstantin Malkov"-Sadovo, Bulgaria during 2013-2015 growing seasons. Twenty two einkorn wheat accessions were evaluated to estimate of variability, heritability, genetic advance and associations among characters. The values of mean square for all twelve characters showed highly significant differences between einkorn genotypes. The phenotypic coefficients of variation were higher than genotypic coefficient of variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Consequently, lines sown in spring having shorter stems were observed to be more resistant to lodging, whereas those sown in autumn showed moderate lodging near harvesting time. Similar findings for plant heights above 100 cm and severe lodging for einkorn lines were reported in the literatures [33,34,35]. By evaluating morpho-agronomic variability of 1039 einkorn accessions obtained from several world gene banks, it was reported that wild form (T. monococcum subs.…”
Section: Morpho-agronomical Traitssupporting
confidence: 82%
See 2 more Smart Citations
“…Consequently, lines sown in spring having shorter stems were observed to be more resistant to lodging, whereas those sown in autumn showed moderate lodging near harvesting time. Similar findings for plant heights above 100 cm and severe lodging for einkorn lines were reported in the literatures [33,34,35]. By evaluating morpho-agronomic variability of 1039 einkorn accessions obtained from several world gene banks, it was reported that wild form (T. monococcum subs.…”
Section: Morpho-agronomical Traitssupporting
confidence: 82%
“…In this manner, einkorn lines sown in autumn, which exhibited average 93 days more heading time and taller plants, provided higher gross grain yields by producing longer spikes with more spikelets including heavier grains but less glume and protein content than those sown in spring. Similarly, it was reported that the relationship between thousand grain weight, number of spikelets per spike, grain weight per spike and grain yield per plant were to be found significant for 22 einkorn lines [35].…”
Section: Correlations Between Characteristicsmentioning
confidence: 69%
See 1 more Smart Citation
“…It was observed that grain yield/plant and 1000-kernel weight had significant SCA effects (Hassan et al, 2007). Correlation studies (Desheva and Kyosev, 2017) suggested that spike length, 1000-kernel weight, grain weight/spike and grains per spike showed valuable contribution in grain yield, while, grain yield also affected by plants/m 2 and spikes/m 2 significantly (Asrar et al, 2016). The role of peduncle length in yield improvement is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…These results were in agreement with those obtained by (Iqbal et al, 2017), They also found high positive phenotypic correlation for grains/spike with grain weight/spike and spike length with grains/spike. In a correlation study, Desheva and Kyosev (2017) found that 1000-kernel weight, spike length, grain weight/spike and number of grains/spike showed significant and valuable contribution in grain yield. Also, (Gerema et al, 2020) observed positive highly significant correlation for plant height with spike length and tillers with grain yield per hectare.…”
Section: Phenotypic Correlationmentioning
confidence: 99%